Small Bowel Bacterial Overgrowth Syndrome in Patients with Bronchial Asthma - N. D. Potskhverashvili; O. Yu. Zolnikova; N. I. Kokina; N. L. Dzhakhaya; A. V. Sedova; E. L. Bueverova; A. S. Trukhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim.  This work is aimed at studying the role of the small bowel bacterial overgrowth syndrome (SBBOS) in the pathogenesis of bronchial asthma (BA).Materials and methods.  The study included 80 BA patients (45 and 35 patients allergic and non-allergic BA forms, respectively). Conventional laboratory and instrumental studies were conducted. SBBOS was confirmed by a hydrogen breath test with lactulose. Patients received conventional basal therapy with combined drugs (long-acting β2-adrenomimetics, and inhaled glucocorticoids). For SBBOS treatment, rifaximin (23 patients) or rifaximin followed by probiotic (B. bifidum, B. longum, B. infantis, L. rhamnosus) for 1 month (22 patients) was administered. Control studies were conducted on the 14th day and following 1 month of treatment.Results. A frequent combination of the small bowel bacterial overgrowth syndrome and bronchial asthma was revealed. 67 % and 43 % of the patients with the allergic form and non-allergic asthma form, respectively, are shown to suffer from SBBOS, p = 0.028. High levels of IgE (p < 0.01) and eosinophils in sputum (p < 0.001), combined with severe impairment of the function of external respiration (p < 0.01) in the case of SBBOS with allergic asthma reflect a more pronounced degree of sensitization of these patients. The correction of composition disorders of the intestinal microflora is accompanied by a statistically significant decrease in the immune response (p < 0.01) and improvement in the function of external respiration (p < 0.001).Conclusion.  SBBOS is a significant factor, aggravating the course of bronchial asthma and playing an important role in the development and maintenance of sensitization of patients.